On the Origin and Transfer of Dust Aerosols in the Direction of Volzhsky (London Journal of Research In Science: Natural and Formal, 2026)
This article examines forward and backward aerosol transport trajectories for the city of Volzhsky using the HYSPLIT dispersion model, using the example of August 19, 2022. A brief climatic description of summer 2022 conditions conducive to the formation of natural dust is provided.
Keywords: aerosol; dust; HYSPLIT; particles; trajectory